Local distortions about Nd in NdOs4Sb12. Issue 2 (2nd January 2013) - Keiber, T.; Bridges, F.; Baumbach, R. E.; Maple, M. B.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract We present an extended X‐ray absorption fine structure (EXAFS) study of the NdOs4Sb12 system at the Nd and Os LIII edges. Nd is expected to be a "rattler" atom in this skutterudite crystal and we obtain a low Einstein temperature (61 K) as expected. However, although ultrasonic measurements have suggested a large off‐center displacement of Nd, the EXAFS data are inconsistent with such a model. An analysis of the first two Os‐Sb peaks in the Os LIII data also shows no evidence for unusual disorder. In contrast the Nd‐Os peak in the Nd LIII data and the Os‐Os peak in the Os LIII data both show significant disorder at 4 K, with the largest disorder found for the Nd‐Os pair. This suggests that a distortion of the structure that involves mainly the Os atoms is present; it is likely that this distortion ‐ which may also be dynamic ‐ also causes the anomalies in the ultrasonic data (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)